The relationship of family support with the quality of life of hypertension in the elderly - Almaini, Almaini; Sumarni, Titin; Khoirini, Fatimah; Hartoyo, Mugi (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Hypertension is one of the most prevalent chronic diseases among the elderly, significantly affecting their quality of life. In Rejang Lebong, the prevalence of hypertension is 30.71%, with over 60% of the elderly population affected. Health-Related Quality of Life (HRQoL) in elderly individuals with hypertension includes physical, psychological, and social aspects. Family support is a form of interpersonal relationship characterized by attitudes, actions, and acceptance among family members. Families in Rejang Lebong often exhibit a patriarchal structure. Purpose: To examine the relationship between family support and the quality of life of elderly individual swith hypertension. Method: A cross-sectional approach, specially focusing on observational study. The study took place from July-August 2024, in Rejang Lebong, Bengkulu. The independent variable was family support the dependent variables is quality of life. Using purposive sampling and Lemeshow formula, 87 respondent were selected, who met specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondents characteristics, followed by bivariate analysis using spearman rank test. Results: Family support respondents were mostly categorized as high 43 (49.4%) and had a moderate quality of life 64 (73.6%) and significance value (Sig.) <0.05. Conclusion: Indicates most respondent had high family support and moderate quality of life. There is a significant relationship between family support and all domains of quality of life in the elderly with hypertension.